2012
DOI: 10.1186/1865-1380-5-45
|View full text |Cite
|
Sign up to set email alerts
|

Patellar dislocation: cylinder cast, splint or brace? An evidence-based review of the literature

Abstract: Patellar dislocations are a common injury in the emergency department. The conservative management consists of immobilisation with a cylinder cast, posterior splint or removable knee brace. No consensus seems to exist on the most appropriate means of conservative treatment or the duration of immobilisation. Therefore the aims of this review were first to examine whether immobilisation with a cylinder cast causes less redislocation and joint movement restriction than a knee brace or posterior splint and second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…[3][4][5][6]11,12 Multiple randomized control studies and one systematic review have addressed operative vs nonoperative treatment in first-time traumatic patellar dislocations. 1,10,12,16 The area and degree of injury to the MPFL, ligament hyperlaxity, medial retinacular injury, sub-patellar effusion and fractures to bone or cartilage are factors in deciding on surgical management of the dislocated patella. 3,11,13 Some defects may be obvious on examination, however evaluation of the supporting structures of the knee by MRI or computed tomography is important to verify the patency of supporting ligaments and presence of osteochondral fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6]11,12 Multiple randomized control studies and one systematic review have addressed operative vs nonoperative treatment in first-time traumatic patellar dislocations. 1,10,12,16 The area and degree of injury to the MPFL, ligament hyperlaxity, medial retinacular injury, sub-patellar effusion and fractures to bone or cartilage are factors in deciding on surgical management of the dislocated patella. 3,11,13 Some defects may be obvious on examination, however evaluation of the supporting structures of the knee by MRI or computed tomography is important to verify the patency of supporting ligaments and presence of osteochondral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…There is no substantial difference in long-term outcomes between the surgically and conservatively treated patients in regard to redislocation rates, level of activity, or functional and subjective outcomes. 2,3,8,11,16 A randomized study by Nikku et al compared operative vs closed treatment in 125 patients with patellar dislocations without tibiofemoral ligament or osteochondral fractures that necessitated surgical stabilization, with a 2-year follow-up. 2 The results concluded that both treatments gave almost identical outcomes after 2 years in terms of a subjective score, recurrent instability, and function.…”
Section: Operative Vs Nonoperative Carementioning
confidence: 99%
“…Two recent meta-analyses in 2010 8 and 2012 9 could not give us conclusive answers due to a paucity of literature. After thorough literature searches, Smith identified only two studies that met their inclusion criteria, 6,12 and van Gemert et al 9 found an article by Maenpaa and Lehto 6 (1997) to be the only study that met theirs.…”
Section: Immobilization or Early Mobilizationmentioning
confidence: 95%
“…Early immobilization of the knee and the use of crutches is always to be provided immediately after the reduction. It may be useful to administer dietary supplements of chondroitin sulfate and glucosamine, natural elements necessary for the biosynthesis of proteoglycans essential for the health of joint cartilage [63][64][65][66] .…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…Casting has been advocated to allow healing of the medial retinaculum and of the MPFL, but prolonged immobilization results in adverse effects on ligament, bone, cartilage and muscles. The use of braces or tapes could offer faster functional recovery, but with a longer time for MPFL healing [91][92][93] .…”
Section: Taping Bracing and Castingmentioning
confidence: 99%